EPILEPSY ASSOCIATED WITH TUMORS BRAIN IN CHILDREN. (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Today it is believed that it is not the tumor itself that is epileptogenic, but the brain changed under its influence. Hence, it is believed that removal of only the tumor will not necessarily lead to the absence of seizures, but once the GBM is removed, the peritumoral tissue will normalize and epileptic seizures will disappear. The impact of the radical removal of the tumor and the need to remove the surrounding brain tissue on the course of seizures is discussed, but in general, radical removal is much more effective in eliminating epilepsy.